Genetics and Pathogenic of (SARS-Covid-19) Coronavirus (Article Review) - AL-Fatlawy, Hawraa Natiq Kabroot; Mohammed, Zainab Sajid; Hamza Al-Kraity, Asst.Prof.Dr. Wijdan Rajh (Medical Science Journal for Advance Research, 2023)
Background: Coronaviruses are a group of enveloped viruses with non-segmented, single-stranded, and positive-sense RNA genomes. These viruses can infect various important vertebrates such as pigs and chickens, as well as humans, causing respiratory diseases. Among them, there are two highly pathogenic coronaviruses that have resulted in global outbreaks: the severe acute respiratory syndrome coronavirus (SARS-CoV) and the Middle East respiratory syndrome coronavirus (MERS-CoV). The name "coronavirus" comes from the outer fringe, or "corona," of embedded envelope protein. The Coronaviridae family can cause a wide range of animal and human diseases. The RNA genome replication process is unique in that it generates a nested set of viral mRNA molecules. Human coronavirus (H-CoV) infection can cause respiratory diseases with varying degrees of severity. COVID-19 can cause a variety of symptoms that vary in severity. While many cases may not result in any symptoms or only mild ones, some patients may experience a more severe form of the disease that can lead to acute respiratory distress syndrome and other complications affecting multiple organs.